Convection Study by PIV Method Within Horizontal Liquid Layer Evaporating Into Inert Gas Flow; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Kreta A. Aleksei (2016, 2016)
Title screen